The combined effects of grain and sample sizes on the mechanical properties and fracture modes of gold microwires. Issue 1 (January 2019) - Yang, H.K.; Cao, K.; Han, Y.; Wen, M.; Guo, J.M.; Tan, Z.L.; Lu, J.; Lu, Y.
Abstract: Hall-Petch relation was widely applied to evaluate the grain size effect on mechanical properties of metallic material. However, the sample size effect on the Hall-Petch relation was always ignored. In the present study, the mechanical test and microstructure observation were performed to investigate the combined effects of grain and sample sizes on the deformation behaviors of gold microwires. The polycrystalline gold microwires with diameter of 16 μm were annealed at temperatures from 100 °C to 600 °C, leading to different ratios ( t/d ) of wire diameter ( t ) to grain size ( d ) from 0.9 to 16.7. When the t/d was lower than 10, the yield stress dropped fast and deviated from the Hall-Petch relation. The free-surface grains played key role in the yield stress softening, and the volume fraction of free-surface grains increased with the t/d decreasing. Furthermore, the effects of t/d on work-hardening behaviors and fracture modes were also studied. With t/d value decreasing from 17 to 3.4, the samples exhibited necking fracture and the dislocation pile-ups induced work-hardening stage was gradually activated. With the t/d value further decreasing ( t/d < 3.4), the fracture mode turned into shear failure, and the work-hardening capability lost. As the gold microwire for wire bonding is commonly applied in the packaging of integrated circuit chips, and the fabrication of microwire suffers multi-pass cold-drawing and annealing treatments to control the grain size. The present study could provide instructive suggestion for gold microwire fabrication and bonding processes.